Studi Penelusuran (Tracer Study) Lulusan Program Studi Pendidikan Teknik Bangunan FT UNJ Tahun Lulus 2006-2011 - Ria Riantik Sari (LPPM Universitas Negeri Jakarta, 2015)
This study aims to gain knowledge and an overview based on data or facts right and can be trusted on the map of employment and capture feedback on the profile of occupations graduate Studies Program of Technical Education Building FT UNJ who live in Jabodetabek.The research was conducted on graduates of Technical Education Building Program that has been passed in 2006 through 2011. This research uses descriptive method with survey approach. The population in this study amounted to 127 people and the sample amounted to 55 people.From the results of this study was obtained that the majority of the work of Technical Education Program graduates working in the field of building non-education as a force in the field of contracting technical staff, consultants and in fields such as banking and entrepreneurial economy. And minority work graduate Studies Program of Technical Education Building work in the field of vocational education as a teacher, junior high, elementary school and a tutor. The waiting period respondents averaged less than 3 months. Sources of information obtained from a majority of respondents work print / electronic, while the rest is obtained from friends / relations. Salaries earned an average of Rp. 2,500,001 - Rp. 3 million per month with an average service life of 13-18 months. Suitability of work graduate education courses with competency building technique that is 6 people or 10.91% of 48 respondents have field work related to building techniques, while respondents who work outside the engineering field of building as many as 7 people or 12.73% . Employment status of graduates of the majority is not fixed.